CRAYON SHIN-CHAN: APAKAH KOMIK JEPANG MENDIDIK? - Syam, Essy (Universitas Lancang Kuning, 2008)
Comic is not familiar reading book for most Indonesians, particularly Indonesian children because in Indonesia, most comic readers are children. There is no information when and why most Indonesian people assume that comics are reading books for children. In its original country, Japan, comic is not only read by children, instead Japanese society has various kinds of comics based on their reader groups. In Indonesia, comic is considered as reading for children may be caused by its simple and educated content. But is it true that all comics educate children? Crayon Shin-Chan is a comic familiar to Indonesian people. In Japan, Crayon Shin-Chan is not read by children because this comic is written for adults. For that reason, in this comic, there are found expressions which are understood by adults, thus not suitable for children. Although the main character of the comic is a child, this comic is written for adult readers. By so, this comic educative for children because it contains impolite expressions expressed by a child to his parents or to older people, besides it is also contains physical violence done mostly by mother to the child. Both physical violence and impolite expressions found in the comic may contribute negatively to children's morality. It is for that reason that this comic is not educative for children.